2005
DOI: 10.1111/j.0014-3820.2005.tb01023.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Genetic Effects on Offspring Fitness Are Context Dependent: Within the Extrapair Mating System of a Socially: Monogamous Passerine

Abstract: Abstract. Avian extrapair mating systems provide an interesting model to assess the role of genetic benefits in the evolution of female multiple mating behavior, as potentially confounding nongenetic benefits of extrapair mate choice are seen to be of minor importance. Genetic benefit models of extrapair mating behavior predict that females engage in extrapair copulations with males of higher genetic quality compared to their social mates, thereby improving offspring reproductive value. The most straightforwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…However, the relative survival of EPY and WPY and therefore the fitness consequences of EPP for females did not vary with season. By contrast, the only other study system where differential survival of EPY and WPY in early versus late broods was estimated showed that coal tit EPY had higher recruitment if hatched late in the season but tended to have lower recruitment if hatched early in the season, with no average effect of extra-pair status across all broods [34]. If anything, EPY on Mandarte tended to be less likely to survive from ringing to recruitment if hatched late in the season (table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relative survival of EPY and WPY and therefore the fitness consequences of EPP for females did not vary with season. By contrast, the only other study system where differential survival of EPY and WPY in early versus late broods was estimated showed that coal tit EPY had higher recruitment if hatched late in the season but tended to have lower recruitment if hatched early in the season, with no average effect of extra-pair status across all broods [34]. If anything, EPY on Mandarte tended to be less likely to survive from ringing to recruitment if hatched late in the season (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, any increased fitness of EPY has been predicted to be primarily manifested under poor conditions, such as late in the breeding season [3335]. Since such sex- or environment-specific variation may alter the magnitude of any overall indirect benefit of extra-pair reproduction [32,34,36], rigorous studies comparing fitness components between EPY and WPY should explicitly quantify sex- and environment-specific effects.…”
Section: Introductionmentioning
confidence: 99%
“…This idea has only formally been tested a handful of times, but these early studies have proved promising (Schmoll, ). In coal tits ( Periparus ater ), EPO were more likely to recruit into the breeding population than were WPO, but only if they had been born late in the season when overall breeding performance had declined (Schmoll et al, ). Likewise, common yellowthroat ( Geothlypis trichas ) EPO exhibited a stronger T‐cell‐mediated immune response than WPO only in the colder of two study years (Garvin, Abroe, Pedersen, Dunn, & Whittingham, ).…”
Section: Introductionmentioning
confidence: 99%
“…Three factors might have caused problems with the estimation of indirect benefits to date. First, genetic effects might be context dependent and thus manifested only under some environmental conditions (Sheldon 2000a; Schmoll et al. 2005; Garvin et al.…”
Section: Introductionmentioning
confidence: 99%